Investigating access to periodic markets in rural China. (February 2022) - Liu, Zhengying; Liu, Qiyang; Zhao, Pengjun; Tang, Junqing; Gong, Zhaoya
Abstract: There has been a lack of clear understanding of the characteristics and correlates of rural residents' access to periodic markets. This study contributes to the new evidence for this by using data from face-to-face interviews with 4777 rural residents from 276 villages across China. The results show that village terrain is substantially associated with access to periodic markets. Rural residents living in the mountain, high plateau, and hilly areas are more likely to travel a long distance to the nearest periodic market than those living in the plain area. The proximity of the town center positively relates to access to periodic markets. In addition, we found a larger number of shop point of interests within a 2000 m circular buffer around the village center associate with better access to the neatest periodic market. These findings offer new insights for policymaking on improving access to periodic markets for residents in rural areas.